Evaluation of information and advisory support received by the farmers in Jaffna, Sri Lanka - Suvanthini., S; Thirukkumaran, G (Applied Science Research, 2016)
Jaffna is one of the main agricultural districts in the Northern Province, Sri Lanka. Farmers in this district rely on traditional practices and experience gained from previous generation. Advisory support and information with new technologies assist farmers to increase the production and get high income from their cultivation. Present investigation was made to evaluate the advisory support and information received by the farmers in Jaffna. Primary data and secondary data was collected by using structured questionnaire and interviews during the period from August 2014 to June 2015.All the results were analyzed by using SPSS and Microsoft excel. The results revealed that awareness about the advisory support is low when compared to farmers who know about the services. Mass media played considerable role to give the information for farmers. Among the mass media newspaper scored maximum response which is observed as 96.77%. Both government and non - governmental organizations gave the services on production and protection techniques. But the time constraint and as they are doing traditional farming were limited to access these information. Even though, strong positive correlation was observed between awareness and the income. This study ensures that effective advisory support and information make the farmers towards to do the farming with appropriate knowledge.
Keywords: Advisory support; farmers; mass media; income; Jaffna; newspaper